The Use of Figurative Language in the Saur Matua Ceremony: A Linguistic and Cultural Analysis of Batak Toba Oral Traditions? - Tampubolon, Marlina; Sinaga, Dwi Febrina; Harahap, Nurul Husnah; Sitompul, Monika Sales (Institute of Computer Science (IOCS), 2025)
Language and culture are interrelated and form a unity that reflects the values of a society. In the context of the Saur Matua traditional ceremony of the Batak Toba tribe, the use of figurative language is an important element that conveys cultural values such as kinship, religiosity, descent, wealth, and honor. This study aims to analyze the forms and meanings of figurative language (umpasa) used by Hula-hula, Dongan Tubu, and Parboru in the Saur Matua ceremony. Using a descriptive qualitative method, data were collected through direct observation, audio-video documentation, and informal interviews with 12 key informants consisting of community leaders, traditional elders, and participants of the ceremony. The data were analyzed through transcription, classification of types of figurative language, and interpretation of cultural meanings based on literary linguistic theory. The results reveal that umpasa is predominantly used to deliver prayers and hopes, moral advice, and motivation to the bereaved family. Similes and symbols are the most frequently used figures of speech. The use of figurative language in this ceremony not only enhances the aesthetic aspect of communication but also plays a vital role in preserving the noble values of Batak Toba culture. Academically, this study contributes to the enrichment of cultural linguistic research and supports the preservation and documentation of Indonesian oral literature, particularly among indigenous communities.